'The half I keep': John Berger's Booker Prize speech fifty years later. (October 2022) - Hudson, Martyn
Fifty years after John Berger's controversial acceptance speech for the Booker Prize in 1972, in which he highlighted Booker McConnell's involvement in the colonial exploitation of the Caribbean and announced that he would donate half of the prize money to the British Black Panthers and use the other half to research the situation of European migrant workers, the author reflects on the implications of the speech for anti-racist struggle in the 1970s and today, as well as the direction of Berger's work after this pivotal intervention.